Comparison of photophysiological characteristics of two strains of the cyanobacterium Trichodesmium in relation to nitrogen fixation - Míšková, Anežka Terezie (Jihočeská univerzita, 2023)
Photophysiological characteristics related to nitrogen fixation were studied and compared between two strains (IMS101 and NIBB1067) of the cyanobacterium Trichodesmium. To re-evaluate the hypothesis about the relation between nitrogen fixation and phycobilisomes uncoupling, fluorescence lifetime measurements were performed at bulk level using Time-resolved fluorescence spectroscopy and at single-cell resolution using Fluorescence-lifetime imaging microscopy (FLIM). Combination of FLIM with Lugol's stain allowed to directly relate fluorescence lifetime to staining pattern of a commonly used marker of N2 fixing cells.
Comparison of photophysiological characteristics of two strains of the cyanobacterium Trichodesmium in relation to nitrogen fixation
Keywords: Trichodesmium; Nitrogen fixation; Photosynthesis; Phycobiliproteins; Fluorescence Lifetime; Trichodesmium; Nitrogen fixation; Photosynthesis; Phycobiliproteins; Fluorescence Lifetime